Student government: the European experience - Koralevski, J. (Problems of Engineer-Pedagogical Education, 2018)
The problem of formation and development of the institution of student government in Europe was concidered. It is proved that the system of student self-governance in higher education institutions of European countries develop on the basis of historical, cultural and educational traditions of the respective European countries. It is shown that the student government is now in the European Union can be represented as an independent community of students by implementing control functions higher education institution with a specially created formal institutions. Thus it has a number of different forms: student parliaments, committees, and communities, councils of elders and others. Attention is drawn to the main objectives being realized student government, including the development and improvement of educational process on the basis of innovative technologies; assistance in solving organizational, cultural, social, housing and other problems of students; creating conditions conducive to the formation of students' personal and business skills necessary for their maximum professional fulfillment.